CXCL8 is associated with aflatoxin B1–triggered injury and caspase-3 activation in porcine kidney epithelial PK15 cells: integrated transcriptomics and CRISPR/Cas9 knockout - Jianlin Yuan; Yuhan Ma; Jinfeng Li; Xizhu Chen; Yiping Wen; Rui Wu; Xinfeng Hang; Heng Huang; Senyan Du; Yiping Wang; Qi-Gui Yan; Xiaobo Huang; et al. (Food and Chemical Toxicology, 2026)

Intravenous Exposure to Amino-polystyrene Induces Excessive Autophagy and Apoptosis in Myocardium Through ROS Driven PI3K/AKT/mTOR Axis - Wen Gou; Yujun Xie; Rui Xia; Ping Gou; Chunfeng Cao; Fujun Luan; Beizhong Liu; Yuan Li (Cardiovascular Toxicology, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

Distributed nonlinear placement problems in the NASVs with nonsmooth objectives and unknown time-varying actuator faults - Wen-Jin Liu; Rui-Qi Cao; Xinxin Zhang; Xiang-Yu Yao; Ming-Feng Ge (Ocean Engineering, 2026)

Relationship of catalytic performance and catalyst structure evolution based on pressurized CH4-CO2 reforming reaction over carbon-supported Co-Ir alloy catalysts - Wen Tang; Jing-Pei Cao; Xiao-Yan Zhao; Dan Xie; Kai-Rui Luan; Chang-Jiang Li; Qi-Ming She; Tungalagtamir Bold (Fuel, 2026)

Synergistic effects of internal FeB doping and external SiC/C dual coating on micro-Si anode performance - Shuai Wang; Qinyu Wu; Rui Cao; Zhenfei Cai; Xiaolong Ma; Zhongqiu Chu; Zhuo Zhao; Yangzhou Ma; Guangsheng Song; Cuie Wen (Chemical Engineering Journal, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

The microbial mechanism of the impact of grazing degradation on the soil multifunctionality of the hummock wetland on the riverscape - Xiaoai Cao; Huamin Liu; Rui Zhang; Yunhao Wen; Shan Jiang; Zhichao Xu; Lu Wen; Yi Zhuo; Dongwei Liu; Ke Yu; Lixin Wang (Applied Soil Ecology, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Variations in C:N:P Stoichiometry, Non-Structural Carbohydrate, Chlorophyll, and Hormones of Abelmoschus manihot Flower at Different Phenological Growth Stages - Wen-zhang Qian; Hong-rui Wang; Shao-jun Fan; Yi-xiao Xiao; Yun-yi Hu; Guo-xing Cao; Shun Gao (Journal of Plant Growth Regulation, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Deciphering the molecular mechanisms of oil palm lipid metabolism through combined metabolomics and transcriptomics - Jerome Jeyakumar John Martin; Wen Xu; Xinyu Li; Xiaoyu Liu; Lixia Zhou; Rui Li; Dengqiang Fu; Qihong Li; Hongxing Cao (Food Chemistry, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Salinicoccus bachuensis sp. nov., a novel halophilic bacterium, isolated from rhizosphere soil surrounding Tamarix chinensis Lour. plants in Bachu County, Xinjiang, China - Zhen-Pu Liang; Rui Wang; Han-Wen Cao; Xin-Lu Zhou; Jin-Ping Dai; Ping Su; Deepali Singh; Xiao-Xia Zhang (Archives of Microbiology, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Unveiling the nonlinear relationships and co-mitigation effects of green and blue space landscapes on PM2.5 exposure through explainable machine learning - Wei Cao; Liyan Wang; Rui Li; Wen Zhou; Deshun Zhang (Sustainable Cities and Society, 2025)

In-situ experiments of dynamic microscopic reaction for CO2-brine-carbonate system - Yulong Zhao; Yongchao Wang; Shaomu Wen; Liehui Zhang; Zhenglin Cao; Zihan Zhao; Wei Xiong; Cheng Cao; Rui Tang; Yunting Fan; Zehao Xie; Ruihan Zhang; et al. (Chemical Engineering Journal, 2025)

TP53 to mediate immune escape in tumor microenvironment: an overview of the research progress - Kai-li Zhu; Fei Su; Jing-ru Yang; Ruo-wen Xiao; Rui-yue Wu; Meng-yue Cao; Xiao-ling Ling; Tao Zhang (Molecular Biology Reports, 2024)
Increasing evidence suggests that key cancer-causing driver genes continue to exert a sustained influence on the tumor microenvironment (TME), highlighting the importance of immunotherapeutic targeting of gene mutations in governing tumor progression. TP53 is a prominent tumor suppressor that encodes the p53 protein, which controls the initiation and progression of different tumor types. Wild-type p53 maintains cell homeostasis and genomic instability through complex pathways, and mutant p53 (Mut p53) promotes tumor occurrence and development by regulating the TME. To date, it has been wildly considered that TP53 is able to mediate tumor immune escape. Herein, we summarized the relationship between TP53 gene and tumors, discussed the mechanism of Mut p53 mediated tumor immune escape, and summarized the progress of applying p53 protein in immunotherapy. This study will provide a basic basis for further exploration of therapeutic strategies targeting p53 protein.

Deep learning reconstruction of high-Reynolds-number turbulent flow field around a cylinder based on limited sensors - Rui Li; Baiyang Song; Yaoran Chen; Xiaowei Jin; Dai Zhou; Zhaolong Han; Wen-Li Chen; Yong Cao (Ocean Engineering, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

Characteristics, sources, and health risk assessment of atmospheric particulate mercury in Guanzhong Basin - Xiaofei Li; Rui Zhang; Lekhendra Tripathee; Feng Yu; Jingning Guo; Wen Yang; Junming Guo; Shichang Kang; Junji Cao (Environmental Pollution, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

CD4 is an important host factor for Japanese encephalitis virus entry and replication in PK-15 cells - Qi Wang; Shuqing Yang; Ke Yang; Xinran Li; Yu Dai; Yi Zheng; Sanjie Cao; Qigui Yan; Xiaobo Huang; Yiping Wen; Qin Zhao; Senyan Du; et al. (Veterinary Microbiology, 2023)

The predictive, preventive, and personalized medicine of insomnia: gut microbiota and inflammation - Hao-Wen Chen; Rui Zhou; Bi-Fei Cao; Kuan Liu; Qi Zhong; Yi-Ning Huang; Hua-Min Liu; Jin-Qing Zhao; Xian-Bo Wu (EPMA Journal, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

IFN-γ promotes PANoptosis in Pasteurella multocida toxin-induced pneumonia in mice - Hang Xiao; Qin Zhao; Jianlin Yuan; Wei Liang; Rui Wu; Yiping Wen; Senyan Du; Yiping Wang; Shan Zhao; Yifei Lang; Qigui Yan; Xiaobo Huang; et al. (Veterinary Microbiology, 2023)

Insights into dissolved organics in non-urban areas - Optical properties and sources - Feng Yu; Xiaofei Li; Rui Zhang; Jingning Guo; Wen Yang; Lekhendra Tripathee; Lang Liu; Yuqin Wang; Shichang Kang; Junji Cao (Environmental Pollution, 2023)

Nanostructured carboxylated-wood aerogel membrane for high-efficiency removal of Cu (II) ions from wastewater - Wen He; Jizhou Cao; Feiyu Guo; Zhihao Guo; Peiguo Zhou; Rui Wang; Shuang Liang; Qunyan Pang; Bairen Wei; Yue Jiao; Tripti Singh; Qiliang Fu (Chemical Engineering Journal, 2023)

A Novel D-π-A Type Fluorescent Probe for Cu2+ Based on Styryl-Pyridinium Salts Conjugating Di-(2-picolyl)amine (DPA) Units - Rui Cao; Mengyu Zhang; Wen Tang; Jing Wu; Meixiang Wang; Xiaoxiao Niu; Zhaodi Liu; Fuying Hao; Huajie Xu (Journal of Fluorescence, 2023)

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

Highly efficient aerobic oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid over halloysite nanotubes-templated nitrogen-doped carbon supported bimetallic AuPd catalyst - Fang Wang; Changhao Yan; Rui Jiang; Yao Chen; Yanan Wei; Yu Cao; Wen Guan; Pengwei Huo; Yunlei Zhang (Applied Clay Science, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

B-YOLOX-S: A Lightweight Method for Underwater Object Detection Based on Data Augmentation and Multiscale Feature Fusion - Jun Wang; Shuman Qi; Chao Wang; Jin Luo; Xin Wen; Rui Cao (Journal of Marine Science and Engineering, 2022)
With the increasing maturity of underwater agents-related technologies, underwater object recognition algorithms based on underwater robots have become a current hotspot for academic and applied research. However, the existing underwater imaging conditions are poor, the images are blurry, and the underwater robot visual jitter and other factors lead to lower recognition precision and inaccurate positioning in underwater target detection. A YOLOX-based underwater object detection model, B-YOLOX-S, is proposed to detect marine organisms such as echinus, holothurians, starfish, and scallops. First, Poisson fusion is used for data amplification at the input to balance the number of detected targets. Then, wavelet transform is used to perform Style Transfer on the enhanced images to achieve image restoration. The clarity of the images and detection targets is further increased and the generalization of the model is enhanced. Second, a combination of BIFPN-S and FPN is proposed to fuse the effective feature layer obtained by the Backbone layer to enhance the detection precision and accelerate model detection. Finally, the localization loss function of the prediction layer in the network is replaced by EIoU_Loss to heighten the localization precision in detection. Experimental results comparing the B-YOLOX-S algorithm model with mainstream algorithms such as FasterRCNN, YOLOV3, YOLOV4, YOLOV5, and YOLOX on the URPC2020 dataset show that the detection precision and detection speed of the algorithm model have obvious advantages over other algorithm networks. The average detection accuracy mAP value is 82.69%, which is 5.05% higher than the benchmark model (YOLOX-s), and the recall rate is 8.03% higher. Thus, the validity of the algorithmic model proposed in this paper is demonstrated.

Bionic study of the cushioning and energy-saving joints of leg of the walking robot - Rui Zhang; Wenchao Dong; Lujiang Liu; Xuemei Ju; Hao Pang; Qingqiu Cao; Lige Wen (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Comparative transcriptome analysis reveals that deletion of CheY influences gene expressions of ABC transports and metabolism in Haemophilus parasuis - Lvqin He; Xuefeng Yan; Ke Dai; Xintian Wen; Sanjie Cao; Xiaobo Huang; Rui Wu; Qin Zhao; Yong Huang; Qigui Yan; Xiaoping Ma; Xinfeng Han; et al. (Functional & Integrative Genomics, 2021)

Tamlana haliotis sp. nov., isolated from the gut of the abalone Haliotis rubra - Wen-Rui Cao; Bang-Tao Liu; Xun-Ke Sun; Yuan-Yuan Sun; Ming-Yu Jiang; Zong-Jun Du (Archives of Microbiology, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Ruegeria haliotis sp. nov., Isolated from the Gut of the Abalone Haliotis rubra - Wen-Rui Cao; Dan-Dan Shang; Bang-Tao Liu; Yi-Hao Hu; Xun-Ke Sun; Yuan-Yuan Sun; Ming-Yu Jiang; Zong-Jun Du (Current Microbiology, 2021)

Development of global soil erosion research at the watershed scale: a bibliometric analysis of the past decade - Xuan Huang; Kai-Rui Wang; Yu-wen Zou; Xin-Chun Cao (Environmental Science and Pollution Research, 2021)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

Genomic changes in an attenuated genotype I Japanese encephalitis virus and comparison with virulent parental strain - Yuyong Zhou; Rui Wu; Yao Feng; Qin Zhao; Xintian Wen; Xiaobo Huang; Yiping Wen; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; Sanjie Cao (Virus Genes, 2018)

Mutation of I176R in the E coding region weakens Japanese encephalitis virus neurovirulence, but not its growth rate in BHK-21 cells - Yuyong Zhou; Rui Wu; Qin Zhao; Yung-Fu Chang; Xintian Wen; Yao Feng; Xiaobo Huang; Yiping Wen; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; et al. (Archives of Virology, 2018)

Production of Humic Acid by a Bacillus megaterium Strain Using Vinasse - Nan Li; Zhi-Nian Deng; Yuan-Wen Wei; Hui-Qing Cao; Yang-Rui Li (Sugar Tech, 2018)

Polyamine-binding protein PotD2 is required for stress tolerance and virulence in Actinobacillus pleuropneumoniae - Zhuang Zhu; Qin Zhao; Yu Zhao; Fei Zhang; Xintian Wen; Xiaobo Huang; Yiping Wen; Rui Wu; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; et al. (Antonie van Leeuwenhoek, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Construction of a bivalent DNA vaccine co-expressing S genes of transmissible gastroenteritis virus and porcine epidemic diarrhea virus delivered by attenuated Salmonella typhimurium - Yudi Zhang; Xiaohui Zhang; Xiaodan Liao; Xiaobo Huang; Sanjie Cao; Xintian Wen; Yiping Wen; Rui Wu; Wumei Liu (Virus Genes, 2016)

Phylogenetic analysis reveals that Japanese encephalitis virus genotype III is still prevalent in swine herds in Sichuan province in China - Rui Wu; Qiao Wang; Hongming Liu; Chunxia Chai; Bo He; Xiaobo Huang; Yiping Wen; Xintian Wen; Qiguai Yan; Xiaoping Ma; Sanjie Cao (Archives of Virology, 2016)

Immunogenicity of transmissible gastroenteritis virus (TGEV) M gene delivered by attenuated Salmonella typhimurium in mice - Ying Qing; Jiawen Liu; Xiaobo Huang; Yaqing Li; Yudi Zhang; Jie Chen; Xintian Wen; Sanjie cao; Yiping Wen; Rui Wu; Qigui Yan; Xiaoping Ma (Virus Genes, 2016)

Lysobacter chengduensis sp. nov. Isolated from the Air of Captive Ailuropoda melanoleuca Enclosures in Chengdu, China - Caifang Wen; Lixin Xi; Rong She; Shan Zhao; Zhongxiang Hao; Lu Luo; Hong Liao; Zhenrong Chen; Guoquan Han; Sanjie Cao; Rui Wu; Qigui Yan; et al. (Current Microbiology, 2016)

Detection and differentiation of Japanese encephalitis virus genotype I and genotype III by reverse transcription loop-mediated isothermal amplification combined with restriction fragment length polymorphism - Liang Zhang; Sanjie Cao; Rui Wu; Shuquan Zhu; Hanyang Liu; Lei Yuan; Shuangyan Shi; Dan Zhang; Xiaobo Huang; Xintian Wen; Yiping Wen; Qigui Yan; et al. (Virus Genes, 2015)

First complete genomic characterization of a porcine parvovirus 5 isolate from China - Rui Wu; Yiping Wen; Xiaobo Huang; Xintian Wen; Qiguai Yan; Yong Huang; Xiaoping Ma; Sanjie Cao (Archives of Virology, 2014)

The association between the Lys751Gln polymorphism in the XPD gene and the risk of bladder cancer - Tianyuan Xiong; Jiqiao Yang; Haichuan Wang; Fanyi Wu; Yang Liu; Rui Xu; Zi Lv; Pei Xue; Wen Cao; Yonggang Zhang (Molecular Biology Reports, 2014)

Knockdown of ZNF403 inhibits cell proliferation and induces G2/M arrest by modulating cell-cycle mediators - Rui Guan; Xiao-Yan Wen; Jing Wu; Rongqi Duan; Huibi Cao; Simon Lam; Defu Hou; Youdong Wang; Jim Hu; Zhuchu Chen (Molecular and Cellular Biochemistry, 2012)